Transaction costs and market institutions: grain brokers in Ethiopia - Gabre-Madhin, Eleni Zaude (International Food Policy Research Institute, 1999)
This paper examines the effect of transaction costs of search on the institution of grain brokers in Ethiopia. Primary data are used to derive traders’ shadow opportunity costs of labor and of capital from IV estimation of net profits. A two-step Tobit model is used in which traders first choose where to trade and then choose whether to use a broker to search on their behalf. The results confirm traders’ individual rationality in choosing brokerage, showing high transaction costs are linked to increased broker use while high social capital reduces broker use.